Health in Swedish integration policies : A discourse analysis - Svanholm, Sara; Carlerby, Heidi; Viitasara, Eija (International Journal of Circumpolar Health, 2025)
Previous research has indicated that migrants risk facing inequities both internationally and in Sweden; integration policies are therefore important to study. How health is described in policies affects how health interventions are approached. Discourse analysis offers a way of understanding how health is framed within the integration policies affecting newly arrived migrants in Sweden. The aim was to analyse the health discourses used in Swedish and European Union (EU) integration policies. A discourse analysis, inspired by Fairclough, was performed on integration policies related to Sweden, at local, regional, national and EU levels. The policies of the Establishment Program, which focuses on newly arrived migrants (refugees, persons of subsidiary protection and their relatives who arrived through family reunification), were chosen for the analysis, and 17 documents were analysed in total. The analysis of the documents showed how the health discourses were expressed in the form of the medicalisation of health, the individualisation of health and the risk of ill health. A pathogenic approach to health was visible in the policies and individual disease prevention or rehabilitation was the main health focus. The results showed similarities to previous research highlighting how a particular understanding of health in a neoliberal context is formed.